Study on Computational Thinking as Problem-solving Skill - Comparison Based on Students’ Mindset in Engineering and Social Science - Andik Asmara; Ting-Ting Wu (Journal of Education in Specific Purpose, 2025)
One of the capabilities which 21st-century skill compulsory a person is critical thinking and problem-solving skill that becomes top positions rank. Focus on problem-solving skills can be taught to a child, especially begun in elementary school refer to prior research focus on K-12. Computational thinking was one problem-solving skill that popular to implemented and studied in the current decade. This study was conducted to explore students' capability to be able solving of the problem based on the possibility use the computational thinking way. Participants in this study came from six international students that study in Taiwan and from two deferent sciences disciplines, engineering, and social science. A qualitative method was used to analyze data interview, took example cases from the global issue that is “Climate Change”. The result founded that survive in a new environment was become evidence of their implementation of problem-solving skills. Problem-solving mindset both students of engineering and social science had discrepancy, those are how to use precise structure in the algorithm.